Can the anti-politics machine be dismantled?. Issue 6 (2nd November 2022) - Venugopal, Rajesh
ABSTRACT: This paper engages with a central problem in development studies: why is development so depoliticised, and how can this be remedied? It does so by providing a theoretical/conceptual framework of the way that the 'political' and the 'technical' are constructed as a cognitive gap in the inner frame of the development planner. Drawing on Scott, Schmitt, Weber, Horkheimer & Adorno, and the critical development literature, it argues that politics presents itself to the planner as a sphere of uncertainty that can disrupt project outcomes. Knowledge production about development politics, for example through political economy analysis, is thus a compulsion that arises from the need to govern this source of uncertainty. The politics rendered legible and decoded in this way is also ipso facto no longer part of the political unknown, but now belongs to the realm of the technical. The implications of this framework are that the anti-politics machine will perpetually regenerate itself. The work of mitigating technocratic excess is productive, but it is a Sisyphian labour that will not have a clean or satisfying end-date.